Municipal infrastructure grant and service delivery in Theewaterskloof and Overstrand Municipalities - Majali, Lifa (Graduate School of Business (GSB), 2019)
Rising incidents of misuse and underspending of the municipal infrastructure grant (MIG) by South African municipalities is an increasing concern. Such incidents lead to continuing problems of failure to eradicate infrastructure backlogs and to the poor provision of service delivery by the municipalities. The purpose of this study was to explore the role of the MIG in improving service delivery in Theewaterskloof and Overstrand Municipalities. In doing so, the study aimed to examine the challenges of compliance with MIG conditions, provision of basic services and the exploration of the role of the MIG programme in service delivery. A qualitative research method was undertaken to gain insight into and understanding of the systematic hindrances that prevent Theewaterskloof and Overstrand Municipalities from achieving the MIG objectives of the infrastructure programme. The study used semi-structured questionnaires and multiple face-to-face interviews were conducted with the municipal and provincial officials and community representatives. The research study findings revealed that the MIG programme has had a greater impact on improving the access to basic services for poor communities in Theewaterskloof and Overstrand municipality areas which has resulted in an improvement in the quality of life of those poor communities. Furthermore, when the infrastructure projects take place in the local community, employment and transfer of skills, also take place. The challenges that both municipalities are faced with stem from the ever growing old and new infrastructure backlogs, the maintenance of the ageing infrastructure assets versus the limited funding – there is thus a disparity between the municipal demands and MIG allocation. One of the recommendations provided, given that the municipalities in general in South Africa are struggling to raise co-funding, is that both municipalities should explore public-private partnership as that would alleviate the burden of capital requirements and speed up the reduction of service delivery backlogs.